ANALISIS KEUNTUNGAN USAHATANI BAWANG DAUN DI DESA BONGKUDAI UTARA KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Elsa Novera Mamusung; Leonardus Ricky Rengkung; Celcius ., Talumingan (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze how much profit the farmers get in the activities of scallion farming in North Bongkudai Village, Mooat District, East Bolaang Mongondow Regency. The study was conducted for 3 months from October to December 2018. The data used in this study were primary data and secondary data. Primary data collection is through direct interviews with 60 respondents using the stratified random sampling method. Interviews were conducted based on a previously prepared questionnaire, and secondary data was obtained from the Bolaang Mongondow East Agriculture Office, North Bongkudai Village Office, Sam Ratulangi University Faculty of Agriculture Library, and Local Book Stores. The analysis in this study is qualitative and quantitativeanalysis presented in table form and then described descriptively. The results showed that the amount of profit of the scallion farmers per bed in Bongkudai Utara village in the first strata (lower layer) was Rp.426,664, while for the second strata (middle layer) was Rp.439,185 and for the third strata (upper layer) was Rp. 1,227,853. The highest profit of scallion farmers in Bongkudai Utara Village is in the third strata, reaching Rp1,227,853 per bed.*lrr+eprm*